Transformation of the discourse of globalization in modern social and humanitarian knowledge - Radevich, Ekaterina V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the philosophical and theoretical analysis of the phenomenon of globalization and examines the main conceptual approaches to the study of this phenomenon in socio-humanitarian knowledge. The evolution of the understanding of the globalization process, which in the last decades of the XXI century begins to be interpreted in terms of the risk and instability of the world social space, is traced. This allows us to move from optimistic views on this phenomenon to the stage of reflexive criticism, within which a new model of understanding of the world that is essentially different from the first theoretical models of globalization is built.